Agile-Scrum Implementation in The Development of Kampus Merdeka Information System (Universitas Brawijaya, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) program is a program initiated by the Minister of Education and Culture to encourage students to master various disciplines for their preparation in the job market. At the Institut Teknologi Del, the MBKM program is also offered to students. However, its implementation is not yet fully automated and utilizes various different platforms. This research aims to design and develop the Independent Internship & Study Implementation Information System in the Merdeka Campus at the Institut Teknologi Del using the Agile-Scrum approach. The Scrum method is an iterative software development approach that is flexible to changes. The implementation of Agile-Scrum in the development of the MBKM information system helps achieve goals and automate existing systems. This research involves Scrum activities such as sprint planning, daily scrum, sprint review, and sprint retrospective to produce an information system that meets the requirements. The Scrum product backlog is used as a reference during system development throughout the sprint. The development of the information system through agile-scrum has received feedback during the sprint review and has been functionally tested using several testing methods.